Aid allocation volatility to small island states - Matthew Clarke; Tim Fry; Sandra Mihajilo (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
Aid is an important resource for developing countries. Many small island states (including those in the Pacific) are highly reliant on aid to supplement meagre government resources and other foreign capital inflows. This paper investigates the conditional volatility of aid (for bilateral aid disaggregated into sector aid and programme aid, and multilateral aid) to small island states using an econometric framework. In addition, year-on-year changes in aid allocation are also considered for both changes in aid allocations from major donors to the Pacific as well as for changes in aid receipts in 16 Pacific island countries. The entire sample of countries under consideration includes 44 aid-receiving (small island) states from the regions of Asia-Pacific, Africa and the Americas over the period 1973 to 2004. This paper finds that past aid flows are correlated with present aid flows and that volatility on both sector and programme aid in the Americas and Asia-Pacific region are characterized by a higher degree of volatility than in the African region. An important result of the analysis is that shocks to bilateral aid result in the persistence of volatility for a number of years before stabilizing. This evidence of persistence in volatility, whereby the past levels of volatility influence the degree of volatility that can be expected in the future, implies a certain degree of predictability in the conditional volatility of bilateral aid. The paper also finds that on average multilateral aid is not only considerably more volatile than the bilateral aid, but it is also more unpredictable.
Keywords: F35; 330; aid volatility; small island states; Entwicklungshilfekonditionen; Insel; Kleines-Land-Modell; Pazifischer Raum